Legal Analysis of Electronic Signatures Under Indonesia’s Law No. 11 of 2008 on Electronic Information and Transactions - A. Khaerunnisa Malkab; La Ode Husen; A. Asriati (Manunggal Halim Jaya, 2025)
This research aims to: (1) identify and analyze the legal provisions regarding the validity of electronic signatures within the Indonesian civil law system; and (2) examine and analyze the legal framework governing the verification of electronic signatures as evidence in civil cases according to the prevailing laws and regulations in Indonesia. This study employs a normative juridical research method, using primary data derived from statutory regulations and legal literature. The data were analyzed qualitatively and descriptively by examining the conformity of legal implementation with the principles of evidence in civil procedural law. The research findings indicate that: (1) electronic signatures have legitimate and legally recognized status as long as they meet the requirements stipulated in Article 11 of Law Number 11 of 2008 on Electronic Information and Transactions; and (2) the verification of the validity of electronic signatures follows the general procedures of evidence examination. The study recommends that: (1) there should be increased legal awareness regarding the validity and security of electronic signatures in digital transactions. Intensive public dissemination can help the community understand that legally valid electronic signatures possess the same legal force as conventional signatures, thereby enhancing efficiency and trust in technology-based economic activities; and (2) it is important to strengthen digital legal literacy and capacity through continuous training on electronic evidence and cybersecurity. With a comprehensive understanding, law enforcement officials can assess the validity of electronic signatures objectively and consistently in accordance with the principles of justice and legal certainty.